UPGRADING OF BIO-OIL IN CONTINUOUS CRACKING UNIT - JAMIL, FARRUKH (2013)
Bio-oil from oil palm biomass in Malaysia seems to be attractive due to the resource abundance, environment friendly and to fulfill growing demand of energy. Despite these potentials, its application at commercial scale is limited due to its inevitable properties such as highly acidic, corrosive nature, dense, low energy density and high oxygen content. Upgrading process of bio-oil is an important aspect to raise the bio-oil quality so that it can be used on commercial scale. The available upgrading methods are limited due to some constraints. Based on this, catalytic cracking is selected as most suitable technique to improve quality of bio-oil.